Bakteri dan Multiresisten Obat (Multi Drugresistance) pada Pasien dengan Kateter Urin di RSUD Petala Bumi Pekanbaru - Rita Endriani; Dewi Anggraini; Rachmaliza Rachmaliza; Rika Wandari (Jurnal Ilmu Kedokteran, 2016)
Patients with urinary catheter have an increased risk to get bacteriuria that could be develop to urinary tract infection(UTI). The aim of this study was to know sensitivity pattern and detection of ESBL in bacteria that isolated from urinof patient with urinary catheter more than 48 hours at Petala Bumi Hospital Pekanbaru. Thirty urin spesiments wasgrowthed in blood agar and MacConkey, incubated for 18 – 24 hours. Identification bacteria was done by some ofbiochemical test, sensitivity test was done by Kirby Bauer method, and ESBL detection done by double disc method.Predominantly bacteria isolated was Gram negative (90%). Gram-negative bacteria was 77.7% sensitive tochloramphenicol and fosfomycin. Gram-positive bacteria was 100% sensitive almost all antibiotic tested. Based onscreening test, this study found E. coli (40%) and Klebsiella sp, Acinetobacter sp and Pseudomonas sp (20%) werepossible produce ESBL, but ESBL was not found based on confirmatory test.